Prethermalization and Nonreciprocal Phonon Transport in a Levitated Optomechanical Array. Issue 3 (13th January 2020) - Liu, Shengyan; Yin, Zhang‐qi; Li, Tongcang
Abstract: Recent advances in levitated optomechanics have brought new opportunities for the study of macroscopic quantum mechanics and precision measurement. Previous studies have mainly focused on the single levitated nanoparticle, the systems of multiple levitated nanoparticles were rarely involved. Here an array of optically levitated nanospheres in vacuum is considered and nontrivial phonon transport in this system is investigated. The levitated nanospheres are coupled by optical binding. Key parameters of this system, such as the interaction range, trapping frequencies, and mechanical dissipation, are highly tunable. Due to these advantages, counter‐intuitive phenomena such as prethermalization and nonreciprocal phonon transport can be achieved by tuning the spacing between neighboring spheres, the mechanical dissipation, and the trapping frequency of each sphere. The system provides a great platform to investigate novel phonon transport and thermal energy transfer. Abstract : In this work, the levitated optomechanical array with highly tunable interaction range, trapping frequencies, and mechanical dissipation is studied. Due to the advantages, counter‐intuitive phenomena such as prethermalization and nonreciprocal phonon transport can be achieved. The work presents a platform to investigate novel phonon transport and thermal energy transfer, and gives inspiration on quantum many‐body simulation in the levitated optomechanical system.